A Review of Key Issues and Recent Experiences in Reforming Agricultural Research in Africa - Chema, S.; Gilbert, Elon; Roseboom, Johannes (International Service for National Agricultural Research, 2003)
This study reviews the ongoing reforms of national agricultural research systems (NARS) in sub-Saharan Africa. The study not only takes stock of the principal reform themes (i.e., a redefinition of the role of government, decentralization, stakeholder participation, new financing mechanisms,and system linkages), but also highlights the underlying ideas and concepts that shape the present NARS reform agenda. NARS reform details are illustrated and discussed in seven case-study countries: Côte d'Ivoire, Ethiopia, Ghana, Kenya, Senegal, Tanzania, and Uganda. While there is considerable consensus about the main trends, there are major differences and disputes on specific aspects of the reform agenda. Moreover, NARS reforms alone will not close the technological divide between Africa and the rest of the world-they are to be seen as part of a far broader modernization agenda.